Lactate Is Answerable for Brain Function and Treating Brain Diseases: Energy Substrates and Signal Molecule - Cai, Ming; Wang, Hongbiao; Song, Haihan; Yang, Ruoyu; Wang, Liyan; Xue, Xiangli; Sun, Wanju; Hu, Jingyun (Frontiers in Nutrition, 2022)
Research to date has provided novel insights into lactate's positive role in multiple brain functions and several brain diseases. Although notable controversies and discrepancies remain, the neurobiological role and the metabolic mechanisms of brain lactate have now been described. A theoretical framework on the relevance between lactate and brain function and brain diseases is presented. This review begins with the source and route of lactate formation in the brain and food; goes on to uncover the regulatory effect of lactate on brain function; and progresses to gathering the application and concentration variation of lactate in several brain diseases (diabetic encephalopathy, Alzheimer's disease, stroke, traumatic brain injury, and epilepsy) treatment. Finally, the dual role of lactate in the brain is discussed. This review highlights the biological effect of lactate, especially L-lactate, in brain function and disease studies and amplifies our understanding of past research.